Chylous ascites after lymphadenectomy in a Wilms` tumor patient - Mustafa Asım Yörük; Meryem Erat-Nergiz; Çetin Timur; Aylin Canbolat-Ayhan; Müferet Ergüven (The Turkish Journal of Pediatrics, 2018)
Wilms` tumor is the most common renal malignancy in children and the fourth most common childhood cancer. It accounts 6-7% of all childhood malignancies. Surgical resection is an important therapy option and transabdominal or transperitoneal resection with lymph node sampling is preferred. Development of chylous ascites following intraabdominal or retroperitoneal resection in pediatric age group generally results from extensive lymph node dissection, accidental ligation or interruption of lymphatic ducts. Diseases or conditions affecting abdominal and/or retroperitoneal lymph nodes may cause chylous ascites. Postoperative chylous ascites is associated with significant morbidity and may cause mechanic, nutritional and immunological complications. In the present study, a 16-month-old infant with Stage IV Wilms` tumor who developed chylous ascites after left nephrectomy and lymphadenectomy will be presented; chylous ascites treatment with enteral nutrition and surgical treatment approach for Wilms` tumor will be reviewed.